Pengetahuan Perawat tentang Bantuan Hidup Dasar Berdasarkan AHA Tahun 2015 di UPTD Puskesmas Kota Blitar - Sri Winarni (STIKes Patria Husada Blitar, 2017)
Nurses should be able to perform emergency obedient actions with knowledge base, in Kota Blitar nurses must have certificate of basic life support competence that still valid, nurses must follow the training if the certificate has expired, in Kota Blitar there are nurses who do not know the basic life support procedure that will affect a service quality. The purpose of this research is to know the nurse’s knowledge about basic life support based on AHA 2015 at UPTD Puskesmas Kota Blitar. The research method used descriptive research design, population is 59 nurses of UPTD Puskesmas Kota Blitar, sample of 30 nurses with purposive sampling technique. The data were collected by questionnaire. Result of research 26,7% good knowledge. 70% enough. 3.3% less. Knowledge is sufficient but needs to be upgraded to good in terms of indications of dismissal of basic life support, basic life support arrangements, and an indication of the success of basic life support. Suggestions for research are to conduct competence audits on nurses, and provide opportunities for training and basic life support update information.